The Role of Gratitude in the Construction of Self-Esteem: A Hadith-Based Psychological Analysis of Sunan al-Tirmidhī 2034 - Aryany, Kiki Melania; Khodijah (Journal of Ushuluddin and Islamic Thought, 2023)
This study analyzes the relevance between the concepts of self-esteem and gratitude from the perspective of hadith, with a focus on the hadith narrated by Sunan al-Tirmidhī No. 2034. This hadith is examined through a combined approach of isnād (chain of narrators) and matn (text) criticism and psychological analysis based on Morris Rosenberg’s self-esteem theory. In terms of sanad, the hadith was initially classified as ḍa‘īf, but its quality was upgraded to ḥasan li-ghayrih due to reinforcement from the narration of Ṣaḥīḥ al-Bukhārī. In terms of matn, the hadith is considered sahih because it does not contradict the Qur’an, other stronger hadiths, or common sense. Field studies were conducted through interviews with five informants and measurements using the Rosenberg Self-Esteem Scale (RSE), which showed that individuals with high self-esteem tend to show gratitude, self-acceptance, and optimism. Conversely, individuals with low self-esteem showed symptoms of self-rejection and dissatisfaction, which can be interpreted as a form of ingratitude. These findings confirm that gratitude is a spiritual expression and plays an important role in forming a healthy self-image. Therefore, integrating prophetic values in hadith with a contemporary psychological approach can strengthen individuals’ psychological well-being amid the challenges of modern life.